2015
DOI: 10.1017/s0031182015000724
|View full text |Cite
|
Sign up to set email alerts
|

Phage-fused epitopes fromLeishmania infantumused as immunogenic vaccines confer partial protection againstLeishmania amazonensisinfection

Abstract: Two mimotopes of Leishmania infantum identified by phage display were evaluated as vaccine candidates in BALB/c mice against Leishmania amazonensis infection. The epitope-based immunogens, namely B10 and C01, presented as phage-fused peptides; were used without association of a Th1 adjuvant, and they were administered isolated or in combination into animals. Both clones showed a specific production of interferon-gamma (IFN-γ), interleukin-12 (IL-12) and granulocyte/macrophage colony-stimulating factor (GM-CSF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 78 publications
(200 reference statements)
0
24
0
1
Order By: Relevance
“…Nevertheless, as observed, after the challenge, there was a production of specific anti-SLA antibodies. In BALB/c mice infected with L. amazonensis, the IL-4-dependent production of the IgG1 isotype is associated with disease progression [27,67,68], and the same behaviour is observed in control mice. These data show that non-immunized animals present a susceptible immune phenotype characterized by an inefficient humoral response leading to disease progression, whereas Th1 cytokines from HisAK70-immunized animals together with iNOS and IgG2a production induce a resistant immune phenotype controlling disease progression.…”
Section: Discussionmentioning
confidence: 65%
“…Nevertheless, as observed, after the challenge, there was a production of specific anti-SLA antibodies. In BALB/c mice infected with L. amazonensis, the IL-4-dependent production of the IgG1 isotype is associated with disease progression [27,67,68], and the same behaviour is observed in control mice. These data show that non-immunized animals present a susceptible immune phenotype characterized by an inefficient humoral response leading to disease progression, whereas Th1 cytokines from HisAK70-immunized animals together with iNOS and IgG2a production induce a resistant immune phenotype controlling disease progression.…”
Section: Discussionmentioning
confidence: 65%
“…GM‐CSF has played an important role in the activation, maturation and function of dendritic cells . In the present study, spleen cells from mice vaccinated with rLiHyT/saponin showed higher levels of parasite‐specific GM‐CSF, a molecule linked to the macrophages activation and resistance against infection caused by different Leishmania species, such as L. major , L. donovani , L. infantum and L. amazonensis . In addition, GM‐CSF is able to increase the immunogenicity of antigens that are vaccine candidates, when it was used in some disease models such as malaria , HIV and leishmaniasis .…”
Section: Discussionmentioning
confidence: 51%
“…Peptide mimics of linear and discontinuous protein epitopes, as well as other non-protein antigens, can be affinity purified from RPLs30. The peptide epitope mimics (i.e., mimotopes) used as immunogens are a promising tool for vaccine design, and an efficient means of stimulating the antibody response to native antigens, and providing protection against infection in vivo 31.…”
mentioning
confidence: 99%